2017
DOI: 10.1038/ncomms14574
|View full text |Cite
|
Sign up to set email alerts
|

A potent antimalarial benzoxaborole targets a Plasmodium falciparum cleavage and polyadenylation specificity factor homologue

Abstract: Benzoxaboroles are effective against bacterial, fungal and protozoan pathogens. We report potent activity of the benzoxaborole AN3661 against Plasmodium falciparum laboratory-adapted strains (mean IC50 32 nM), Ugandan field isolates (mean ex vivo IC50 64 nM), and murine P. berghei and P. falciparum infections (day 4 ED90 0.34 and 0.57 mg kg−1, respectively). Multiple P. falciparum lines selected in vitro for resistance to AN3661 harboured point mutations in pfcpsf3, which encodes a homologue of mammalian cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(154 citation statements)
references
References 43 publications
4
150
0
Order By: Relevance
“…Furthermore, related HAT and AAT lead compounds, also 6-amides like AN7973, target Cleavage and Polyadenylation Specific Factor 3 (CPSF3), an endonuclease that functions in mRNA processing 46 . It is known that other oxaboroles inhibit CPSF3 in Plasmodium falciparum 28 , and Cryptosporidium CPSF3 is greater than 40% identical to that of P. falciparum at the amino acid level. It therefore seems possible that AN7973 inhibits Cryptosporidium CPSF3 as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, related HAT and AAT lead compounds, also 6-amides like AN7973, target Cleavage and Polyadenylation Specific Factor 3 (CPSF3), an endonuclease that functions in mRNA processing 46 . It is known that other oxaboroles inhibit CPSF3 in Plasmodium falciparum 28 , and Cryptosporidium CPSF3 is greater than 40% identical to that of P. falciparum at the amino acid level. It therefore seems possible that AN7973 inhibits Cryptosporidium CPSF3 as well.…”
Section: Discussionmentioning
confidence: 99%
“…They typically engage with proteins through interaction of an electrophilic boron atom with nucleophilic partner residues (e.g., serine, threonine or tyrosine) or with metal cations (e.g., Zn 2+ , Mg 2+ ) present in the active site of enzymes, acting as a phosphate mimetic. Potent benzoxaborole inhibitors of bacterial 21,22 , fungal 23 , and protozoan 24 pathogens have been identified that work by inhibiting various essential microbial enzymes 22,23,[25][26][27][28] . Tavaborole, a leucyl-tRNA synthetase inhibitor, is approved for treatment of onychomycosis, and crisaborole, which targets human phosphodiesterase 4, was recently approved for treatment of atopic dermatitis 20,29 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, it is shown that AN3661 is also active against the human malaria parasite P. falciparum (Sonoiki et al , ). Interestingly, T. gondii and P. falciparum parasite lines selected for resistance to AN3661 both harboured mutations in residues located in the active site of CPSF3.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, this should provide an advantage for genome editing, as the introduction of a double strand break in the parasite DNA coupled with homology templates that provide the desired modification should result in consistent homology-directed repair without competing error-prone events. As a result, the application of CRISPR/Cas9 in P. falciparum has relied on donor templates and has been used to knockout genes [8,9], and validate key drug resistance mechanisms [10][11][12]. However the absence of NHEJ, coupled with the low transfection efficiency noted above, has made systematic largescale gRNA-based gene disruption screens that have been revolutionary in other organisms elusive so far [6,13].…”
Section: Introductionmentioning
confidence: 99%